2013
DOI: 10.1007/s00534-013-0596-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis and prevention of postoperative pancreatic fistula after distal pancreatectomy with stapler use

Abstract: The most important risk factor for POPF after DP was suggested to be the thickness of the pancreatic stump, reflecting the volume of remnant pancreas. A triple-row stapler seemed to be superior to a double-row stapler in preventing POPF. However, triple-row stapler use in a thick pancreas is considered to be a future problem to be solved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 24 publications
1
45
1
Order By: Relevance
“…Table 3 shows the impact on POPF of the clinical factors that we tested; no factor was significantly associated with the occurrence of POPF. In previous reports, thick pancreatic parenchyma was significantly associated with an increased incidence of POPF [11,[22][23][24]; however, in our study, the average thickness of the pancreatic parenchyma in PFnegative patients was 10.4卤2.6 mm, which was not significantly different from that of the PF-positive patients (10.1卤 2.2 mm) (P=0.639). Next, we assessed the impact of thickness of the pancreatic parenchyma on the incidence of PF and drain amylase levels.…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…Table 3 shows the impact on POPF of the clinical factors that we tested; no factor was significantly associated with the occurrence of POPF. In previous reports, thick pancreatic parenchyma was significantly associated with an increased incidence of POPF [11,[22][23][24]; however, in our study, the average thickness of the pancreatic parenchyma in PFnegative patients was 10.4卤2.6 mm, which was not significantly different from that of the PF-positive patients (10.1卤 2.2 mm) (P=0.639). Next, we assessed the impact of thickness of the pancreatic parenchyma on the incidence of PF and drain amylase levels.…”
Section: Resultscontrasting
confidence: 83%
“…However, compressing the pancreas itself could cause injury to the pancreatic parenchyma during both techniques, potentially leading to clinically relevant PF, especially in cases with a thick pancreatic parenchyma. Indeed, a thick pancreatic parenchyma is reported to be a risk factor for increased incidence of POPF [11,[22][23][24]. In this context, closure of the pancreatic stump, with minimization of injury to the pancreatic parenchyma, is critical to decreasing the risk of PF after DP.…”
Section: Introductionmentioning
confidence: 98%
“…Several authors investigated the risk factors for POPF after DP with stapler closure [9,11,[22][23][24][25][26][27]. Most of them reported that a thick pancreas was a risk factor for POPF [9,11,22,24,25,27].…”
Section: The Risk Factors For Popf In Procedures Involving Stapler CLmentioning
confidence: 99%
“…Recently, a multivariate analysis identified increased thickness of the pancreatic body as a risk factor for failure with stapled transections. Additionally, use of a double-row (as opposed to a triple-row) stapler load was associated with increased risk of fistula [20].…”
Section: Dissection and Management Of The Pancreatic Stumpmentioning
confidence: 93%